Adoption and implementation of evidence-based library acquisition of electronic resources - Mustafa, A’dillah; Noorhidawati, A. (Malaysian Journal of Library and Information Science, 2020)
Evidence-based librarianship (EBL) has been in the literature for around 20 years, and has received a mixed level of acceptance and adoption in its implementation. The purpose of this study is to identify the determinants of EBL adoption and implementation in library acquisition decision of electronic resources. The Technology-Organization-Environment (TOE) model, Innovation Diffusion Theory (IDT) theory and EBL model were used to form the research framework in order to investigate the adoption and implementation of evidence-based acquisition (EBA). Questionnaires were used as data collection tool. Data were collected from 250 respondents comprising librarians from academic, public and special libraries. The data were analyzed descriptively using Statistical Product and Service Solutions (SPSS) v24. The assessment of the measurement and structural model was executed using Smart-PLS (SEM) 3.0. The reflective model was found to be valid and reliable with the Cronbach’s Alpha above 0.70, CR value and AVE of 0.80-0.90. Fornell-Larcker Criterion and Item Cross-loading recordings revealed that the constructs did not discriminate each other. Path coefficient analysis was performed to test the hypothesis in the identification of significant relationship that resulted in Relative Advantage, Compatibility and Top Management Support as the determinants of EBA of electronic resources Although no significant relationship was found between EBL Adoption and Implementation, an indication of practice was recorded in the level of implementation analysis. Further action and future research for libraries were suggested.